Comparison of Activity Based Costing Unit Costs and Retribution Tariffs for Routine Laboratory Tests - Rivaldi Febrian; Ni Kadek Sucahyaningsih; I Ketut Dian Lanang Triana; Haddan Dongoran; Rukhiyat Syahidin; Ayu Laili Rahmiyati; Vip Paramarta; Kosasih Kosasih (GLOBAL HEALTH SCIENCE GROUP, 2026)
Giri Emas Regional Hospital Laboratory has been applying local government retribution tariffs since 2023. With improvements in operational services and quality, along with the hospital's change in status, there is an increasing need for the implementation of competitive and strategic tariffs. Objective to identify the unit costs of routine laboratory tests using the Activity-Based Costing (ABC) method and compare them with the local government retribution tariffs in Buleleng Regency. Method: The research was conducted using a descriptive quantitative approach from secondary data on laboratory and management records on direct and indirect costs at Giri Emas Regional Hospital from November 1, 2023, to December 31, 2024. The unit cost calculations reveal that certain laboratory tests have significantly higher costs, such as direct bilirubin (IDR 177,951), triglycerides (IDR 174,955), and total bilirubin (IDR 162,541). In contrast, tests like HCG (IDR 38,972) and Widal (IDR 43,020) have the lowest unit costs. Statistically, the median unit cost at Giri Emas Regional Hospital is higher than the local government retribution tariffs (median = 69,186 vs 44,000; U = 47, p < 0.01). Giri Emas Regional Hospital should conduct further evaluation of the differences between its unit costs and the retribution tariffs.